ANALISIS SISTEM KOORDINASI PERPAJAKAN DALAM PENINGKATAN EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI BADAN PENDAPATAN DAERAH KABUPATEN TULANG BAWANG - Ronal Regen; Dora Rinova (e-JKPP, 2021)
The problems in this study are: (1) How is the Analysis of the Tax Coordination System in Increasing the Effectiveness of Collecting Rural and Urban Land and Building Taxes (PBB-P2) at the Regional Revenue Agency of Tulang Bawang Regency? (2) What aspects support and hinder the Tax Coordination System in Increasing the Effectiveness of Rural and Urban Land and Building Taxes (PBB- P2) in the Regional Revenue Agency of Tulang Bawang Regency?This research was a descriptive qualitative research. The use of this method is to describe the Analysis of the Tax Coordination System in Increasing the Effectiveness of Collecting Rural and Urban Land and Building Taxes (PBB-P2) at the Regional Revenue Agency of Tulang Bawang Regency, to examine qualitatively, how all data were obtained directly from informants in the field using interviews and document study.The results showed that the coordination in collecting the Land and Building Tax in Rural and Urban (PBB-P2), in general, the informants supported that the implementation of the PBB-P2 collection coordination system that had been implemented so far had been going well and had an impact on the effectiveness of PBB-P2 revenue. although not optimal. The supporting aspects are seen by the division of labor that has been built and carried out properly according to the tasks in their respective parts, the existence of a good spirit of cooperation, communication has been running effectively, Planning and Formulation of Goals, the mechanism implemented has been running and the parts that have been implemented. existing parts or units run as a system. Then the hindering aspects are the limitations of officers, collection time and communication of collection to taxpayers/community and village/kelurahan is hampered, collection is not optimal and taxpayers/community and village/kelurahan do not submit problematic tax tax data to be corrected, as well as submit object data. /subjects that have not been registered to be registered as potential revenues, and there are still many tax arrears that have not been paid by the taxpayer.